THE HYDROMAGNESITE DEPOSITS OF THE ATLIN AREA, BRITISH COLUMBIA, CANADA, AND THEIR INDUSTRIAL POTENTIAL AS A FIRE RETARDANT - Stamatakis, M. G.; Renaut, R. W.; Kostakis, K.; Tsivilis, S.; Stamatakis, G.; Kakali, G. (Bulletin of the Geological Society of Greece, 2007)
This research examines the potential of the hydromagnesite deposits at Atlin in British Columbia, Canada, for the mineral fire-retardant market. Mineral fire retardants, such as Mg- and Ca/Mg-carbonates, are environmentally friendly, producing non-toxic and non-corrosive gases during their thermal decomposition. During this research, 70 sediment samples and two bulk samples were collected from the study area and analysed. The results showed that the Atlin deposits are composed mostly of hydromagnesite with minor amounts of very fine-grained, soft and platy magnesite. The general conclusion is that the mineralogical composition of the samples, their behavior during thermal decomposition, and their chemical and physical properties, make them suitable for use as white fillers for flame-retardants. Additionally, the whiteness of the samples is sufficient and comparable to other commercial hydromagnesite-bearing rocks. The Atlin reserves of the hydromagnesite ore bodies were overestimated in past literature as 110,000 tons. A more precise calculation of the reserves during a technoeconomic assessment is required.